2003
DOI: 10.1093/jn/133.3.716
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Supplementation Increases Expression of Genes Encoding Interferon-γ, Interleukin-1β, and 3-Methylcrotonyl-CoA Carboxylase, and Decreases Expression of the Gene Encoding Interleukin-4 in Human Peripheral Blood Mononuclear Cells

Abstract: Stimulation of immune cells by antigens triggers changes in the transcription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…This metabolic activation of procarcinogens is a key factor in carcinogenesis of the human prostate [64,65], breast [66], and uterus [67]. Collectively, effects of biotin on gene expression [5,14] and cell signaling [11,12] need to be considered when establishing Tolerable Upper Intake Levels for biotin [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This metabolic activation of procarcinogens is a key factor in carcinogenesis of the human prostate [64,65], breast [66], and uterus [67]. Collectively, effects of biotin on gene expression [5,14] and cell signaling [11,12] need to be considered when establishing Tolerable Upper Intake Levels for biotin [40].…”
Section: Discussionmentioning
confidence: 99%
“…Second, histones (DNA-binding proteins) contain covalently bound biotin [2]; biotinylation of histones might play a role in gene silencing [3], cell proliferation [2,4], and DNA repair or apoptosis [3]. Third, biotin affects gene expression at both the transcriptional [5][6][7] and the posttranscriptional level [6,8,9]. Numerous cell signals have been identified that mediate effects of biotin on gene expression: biotinyl-AMP [10], transcription factors such as NF-κB [11], Sp1 and Sp3 [12], and biotinylation of histones [13].…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of mRNA coding for flavokinase and FAD synthetase was quantified using RT-PCR as described [16,17]; mRNA coding for glyceraldehyde-3-phosphate dehydrogenase was used as a control. The following gene-specific primers were used: 5′-AGA TGG TGG TGA GCA TAG GA-3′ and 5′-CCA CTG CAC TTG GCC TTA AT-3′ for flavokinase; 5′-GTT TGC CGA GTC TCA GTT GT-3′ and 5′-AAT GCC TGG GAA GAG GTA GA-3′ for FAD synthetase; and 5′-ACC ACA GTC CAT GCC ATC AC-3′ and 5′-TCC ACC ACC CTG TTG CTG TA-3′ for glyceraldehyde-3-phosphate dehydrogenase.…”
Section: Reverse Transcriptase Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…The following gene-specific primers were used: 5′-AGA TGG TGG TGA GCA TAG GA-3′ and 5′-CCA CTG CAC TTG GCC TTA AT-3′ for flavokinase; 5′-GTT TGC CGA GTC TCA GTT GT-3′ and 5′-AAT GCC TGG GAA GAG GTA GA-3′ for FAD synthetase; and 5′-ACC ACA GTC CAT GCC ATC AC-3′ and 5′-TCC ACC ACC CTG TTG CTG TA-3′ for glyceraldehyde-3-phosphate dehydrogenase. Only values from within the exponential phase of PCR amplification were considered for analysis by gel densitometry [17].…”
Section: Reverse Transcriptase Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…Supplementation of biotin in cultured human cells modulates the expression of genes related to cell growth and immune response. [4][5][6][7] Furthermore, mRNA of hepatic glucokinase (GCK), an initial glycolytic enzyme, is increased by biotin administration in fasting or streptozotocin (STZ)-induced diabetic rats; [8][9][10][11] in contrast, the gluconeogenic enzyme, phosphoenolpyruvate carboxykinase (PCK1), mRNA inversely decreases. 12) Recently, biotinyl histones have been discovered in biotin-supplemented cultured human cells, and this novel histone modification is thought to repress or enhance classical histone modifications, such as phosphorylation, acetylation and methylation, and to bring about epigenetic alterations in chromatin.…”
mentioning
confidence: 99%